Rising Stars: Astrocytes as a Therapeutic Target for ALS Disease - Izrael, Michal; Slutsky, Shalom Guy; Revel, Michel (Frontiers in Neuroscience, 2020)
Amyotrophic lateral sclerosis (ALS) is a multifactorial disease, characterized by a progressive loss of motor neurons that eventually leads to paralysis and death. The current ALS-approved drugs modestly change the clinical course of the disease. The mechanism by which motor neurons progressively degenerate remains unclear but entails a non-cell autonomous process. Astrocytes impaired biological functionality were implicated in multiple neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS), frontotemporal dementia (FTD), Parkinson’s disease (PD) and Alzheimer disease (AD). In ALS disease patients, A1 reactive astrocytes were found to play a key role in the pathology of ALS disease and death of motor neurons, via loss or gain of function or acquired toxicity. The contribution of astrocytes to the maintenance of motor neurons by diverse mechanisms makes them a promising therapeutic candidate for the treatment of ALS. Therapeutic approaches targeting at modulating the function of endogenous astrocytes or replacing lost functionality by transplantation of healthy astrocytes, may contribute to the development of therapies which might slow down or even halt the progression ALS diseases. The proposed mechanisms by which astrocytes can potentially ameliorate ALS progression and the status of ALS clinical studies involving astrocytes are discussed.